Netizens of Rhetorical Strategy in Responding to President Prabowo Subianto's Political Policy Campaign on Budget Cuts - Helmin Maele; Muslimin; Puspita Dian Agustin (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the forms and identify patterns of netizens' rhetorical strategies in the comments section in response to President Prabowo Subianto's political campaign policy regarding budget cuts. This study uses a qualitative approach with a descriptive qualitative approach. The data analyzed consisted of public comments sourced from the KompasTV YouTube video titled